Hypoxia Enhances Differentiation of Mouse Embryonic Stem Cells into Definitive Endoderm and Distal Lung Cells - Pimton, Pimchanok (Stem Cells Dev, 2015)
We investigated the effects of hypoxia on spontaneous (SP)- and activin A (AA)-induced definitive endoderm (DE) differentiation of mouse embryonic stem cells (mESCs) and their subsequent differentiation into distal pulmonary epithelial cells. SP differentiation for 6 days of mESCs toward endoderm at hypoxia of 1% O(2), but not at 3% or 21% (normoxia), increased the expression of Sox17 and Foxa2 by 31- and 63-fold above maintenance culture, respectively. Treatment of mESCs with 20 ng/mL AA for 6 days under hypoxia further increased the expression of DE marker genes Sox17, Foxa2, and Cxcr4 by 501-, 1,483-, and 126-fold above maintenance cultures, respectively. Transient exposure to hypoxia, as short as 24 h, was sufficient to enhance AA-induced endoderm formation. The involvement of hypoxia-inducible factor (HIF)-1α and reactive oxygen species (ROS) in the AA-induced endoderm enrichment was assessed using HIF-1α(−/−) mESCs and the ROS scavenger N-acetylcysteine (NAC). Under SP conditions, HIF-1α(−/−) mESCs failed to increase the expression of endodermal marker genes but rather shifted toward ectoderm. Hypoxia induced only a marginal potentiation of AA-induced endoderm differentiation in HIF-1α(−/−) mESCs. Treatment of mESCs with AA and NAC led to a dose-dependent decrease in Sox17 and Foxa2 expression. In addition, the duration of exposure to hypoxia in the course of a recently reported lung differentiation protocol resulted in differentially enhanced expression of distal lung epithelial cell marker genes aquaporin 5 (Aqp5), surfactant protein C (Sftpc), and secretoglobin 1a1 (Scgb1a1) for alveolar epithelium type I, type II, and club cells, respectively. Our study is the first to show the effects of in vitro hypoxia on efficient formation of DE and lung lineages. We suggest that the extent of hypoxia and careful timing may be important components of in vitro differentiation bioprocesses for the differential generation of distal lung epithelial cells from pluripotent progenitors.